Electrophoresis deposition of Ag nanoparticles on TiO2 nanotube arrays electrode for hydrogen peroxide sensing - Jiang, Yanshu; Zheng, Baozhan; Du, Juan; Liu, Guangyue; Guo, Yong; Xiao, Dan (Talanta (Oxford), 2013)
In this paper, a simple and green strategy, based on the electrophoresis deposition technology, was reported to prepare Ag nanoparticles (NPs) modified TiO2 nanotube arrays (NTs). The morphologies of AgNPs, TiO2NTs and AgNPs/TiO2NTs were characterized by transmission electron microscope (TEM) and scanning electron microscope (SEM). The results demonstrate that the surface of TiO2NTs was homogeneously decorated with AgNPs, of which the morphology could be easily controlled by the electrophoretic deposition (EPD) time. In order to investigate the co-effects of AgNPs and TiO2NTs on the catalysis of H2O2, the electrochemical performances of TiO2 NTs, AgNPs/Ti and AgNPs/TiO2NTs electrodes were investigated in this work. It is found that the response of AgNPs/TiO2NTs electrode to H2O2 was remarkably enhanced due to the co-effects of AgNPs and TiO2NTs. Therefore, it could be used to fabricate H2O2 sensor. The effects of conditions were investigated in detail, such as EPD time, the operating potential, etc.. Under the optimal experimental condition, the sensor had a quick response to H2O2 at −0.12V with a high sensitivity (184.24mA·M−1cm−2), wide linear range (0.75μM–11.16mM) and low detection limit (85.6nM). In addition, the sensor also has good stability and excellent selectivity. The developed H2O2 sensor has been successfully applied to the detection of H2O2 in real samples. This work also demonstrated that the AgNPs/TiO2NTs has potential application in fabricating glucose sensor by immobilizing glucose oxidase onto the prepared electrode. ► We fabricate a highly dispersed AgNPs modified TiO2NTs structure by EPD technology.► We control the morphology and sensitivity of AgNPs/TiO2NTs electrode by EPD time.► The sensor has a quick response to H2O2 due to the co-effects of AgNPs and TiO2NTs.► The sensor has a low detection limit (85.6nM) to H2O2 with a wide linear range.► The AgNPs/TiO2NTs allows direct electrochemical reactions for glucose oxidase.